Analysis of welfare levels, ecology, and animal management in Seblat Elephant Training Center, Bengkulu−Indonesia - Imtiyaaz, Cassytta Dhiya; Syarifuddin, Amir; Triwanto, Joko; Al Hakim, Rosyid Ridlo (Journal of Biotechnology and Natural Science, 2021)
The Sumatran elephant (Elephas maximus sumatranus) is a large mammal protected species and categorized as endangered according to the IUCN Red List. Habitat management includes control and regulation forest vegetation, open areas, water sources, salting sites, and resting areas for good animal welfare. The Seblat Elephant Training Center (SETC) is a conservation area to protect the Sumatran Elephant from extinction and is an ecotourism destination. This study aimed to analyze the welfare level and management of the Sumatran elephant in the SETC. This research used structured interview method to determine the indicators of the animal welfare level. Calculation of feed productivity and secondary data collection were used to improve the welfare level of the Sumatran Elephant. The research result stated that the welfare level of Sumatran elephant was classified as excellent (the implementation achievement value is 74.3%). In addition, the development of observations suggests that freedom from environmental discomfort needs to be improved by providing quarantine cages and reproductive cages to support natural behavior. Environmental conditions also support the welfare level of the Sumatran elephant.  In conclusion, this facility is properly conducive to the welfare of Sumatran elephants.